2006
DOI: 10.1021/jf060783t
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Genistein and Its Glycoside Genistin As Measured in the Portal Vein of Freely Moving Unanesthetized Rats

Abstract: The present study describes an in vivo bioavailability experiment for genistein and its glycoside genistin, either as pure compounds or from a soy protein isolate extract, using freely moving unanesthetized rats with a cannulation in the portal vein. The results show that genistein is readily bioavailable, being observed in portal vein plasma at the first point of detection at 15 min after dosing. The AUC(0-24h) values for total genistein and its conjugates were 54, 24, and 13 microM h for genistein, genistin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
45
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 32 publications
2
45
0
Order By: Relevance
“…For example, genistein exposure following normal soybean exposure in Asian has been reported to be 50-100 nM [56]. The AUC (0-24h) values for total genistein and conjugates were 54, 24, and 13 μM for genistein, genistin, and enriched protein soy extract, respectively.…”
Section: ) Other Polyphenolsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, genistein exposure following normal soybean exposure in Asian has been reported to be 50-100 nM [56]. The AUC (0-24h) values for total genistein and conjugates were 54, 24, and 13 μM for genistein, genistin, and enriched protein soy extract, respectively.…”
Section: ) Other Polyphenolsmentioning
confidence: 99%
“…These results indicate that the bioavailability of genistein is higher for the aglycone than for its aglycoside. Genistin is partly absorbed in its glycosidic form [56]. It is concluded that bioavailability studies based on portal vein plasma levels contribute to insight into the role of the intestine and liver in deglycosylation and uptake characteristics of glycosylated flavonoids [56].…”
Section: ) Other Polyphenolsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study has proved that the bioavailability of the aglycone form was higher than the glycoside form for isoflavones. 8) A study has shown that glycosylation attenuated the efficiency in inhibiting the xanthine oxidase enzyme and that the aglycone acted as an active chelator of metallic ions. 9) However, to the best of our knowledge, the preventive effect of dietary kaempferol glycoside and its aglycone on diabetes in (type 2) model mice KK-A y has not previously been reported.…”
mentioning
confidence: 99%